2005
DOI: 10.1007/s11745-005-1375-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on the causes for the elevated n−3 fatty acids in cows' milk of alpine origin

Abstract: The influence of grass-only diets either from rye-grass-dominated lowland pastures (400 m above sea level) or botanically diverse alpine pastures (2000 m) on the FA profile of milk was investigated using three groups of six Brown Swiss cows each. Two groups were fed grass-only on pasture (P) or freshly harvested in barn (B), both for two experimental periods in the lowlands and, consecutively, two periods on the alp. Group C served as the control, receiving a silage-concentrate diet and permanently staying in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
198
5
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(232 citation statements)
references
References 42 publications
25
198
5
4
Order By: Relevance
“…Whether this limited effect is due to rapid depletion of reserves, complete metabolization of mobilized polyunsaturated FA or the lack of building reserves of these FA remains unclear. However, the hypothesis that 18:3n-3 in milk could be enhanced by FA composition of mobilized body lipids (Leiber et al, 2005) is not supported by this study.…”
Section: Carry-over Effects Of Pre-calving Fat Supplementation Into Lcontrasting
confidence: 91%
See 2 more Smart Citations
“…Whether this limited effect is due to rapid depletion of reserves, complete metabolization of mobilized polyunsaturated FA or the lack of building reserves of these FA remains unclear. However, the hypothesis that 18:3n-3 in milk could be enhanced by FA composition of mobilized body lipids (Leiber et al, 2005) is not supported by this study.…”
Section: Carry-over Effects Of Pre-calving Fat Supplementation Into Lcontrasting
confidence: 91%
“…One reason hypothesized to be responsible for changes in milk polyunsaturated FA (PUFA) composition is a variation in the endogenous availability of FA reflected by increased levels of b-hydroxybutyrate and non-esterified FA (Leiber et al 2005) in the case of energy-deficient feeding regimes, which cause a negative energy balance. This may lead to body tissue mobilization (Leiber et al 2005(Leiber et al , 2006, which is expected from the study of Raclot (2003) to result in a preferable release of highly unsaturated FA compared with the saturated ones of the same chain-length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the physical and chemical form of PUFA in the hay and to the possible oxidation during storage, part of this FA is saturated through rumen biohydrogenation, and the remaining amount is transferred to milk (Dewhurst et al 2002). The higher CLA content is related to desaturation at the mammary gland level of C18:1 n-7, which is one of the terminal products of rumen biohydrogenation (Leiber et al 2005). The results of this trial showed that GH-milk was characterized by higher contents of C18:3 n-3 and C18:0, whereas C18:1 n-7 was similar in both diets.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of linoleic acid, C18:2n6 (LA), and that of alphalinolenic acid, C18:3n3 (ALA), is dependent on the diet, as these FA cannot be synthesized by the bovine metabolism (MacGibbon and Taylor, 2006). However, most of these fatty acids provided in the diet undergo bacterial modification in the rumen, depending on the feed matrix (Leiber et al, 2005), with LA being the main precursor of CLA. It has been suggested that if the levels of these FA could be increased, milk could be considered a functional food (Bauman and Griinari, 1999;Mattila-Sandholm and Saarela, 2003).…”
mentioning
confidence: 99%